2006
DOI: 10.1097/01.mbc.0000220238.99843.45
|View full text |Cite
|
Sign up to set email alerts
|

Influence of homocysteine on fibrin network lysis

Abstract: To elucidate some of the links between homocysteine and vascular disease, we have evaluated the effect of the amino acid on the formation (by kinetics studies), structure (by electron microscopy) and lysis of the fibrin network, using tissue-type plasminogen activator (t-PA) and urokinase-type plasminogen activator (u-PA). We have studied whether homocysteine could alter the activity of the components involved in fibrinolysis (by amidolytic and thrombolytic methods). The results showed that homocysteine-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 30 publications
0
19
2
Order By: Relevance
“…Homocysteine has also been indicated to have direct effects on fibrin network structure. When fibrin networks were formed from plasma that was incubated with homocysteine, the fibrin network became more compact and more resistant to lysis [48,49]. Black South Africans have been shown to be protected by genetically low levels of homocysteine due its effective metabolism [4].…”
Section: Fibrin Network Structurementioning
confidence: 99%
“…Homocysteine has also been indicated to have direct effects on fibrin network structure. When fibrin networks were formed from plasma that was incubated with homocysteine, the fibrin network became more compact and more resistant to lysis [48,49]. Black South Africans have been shown to be protected by genetically low levels of homocysteine due its effective metabolism [4].…”
Section: Fibrin Network Structurementioning
confidence: 99%
“…Coagulation factor Va is also S-homocysteinylated (Undas et al 2001) and this modification could play a role in the modulation of hemostasis process. Clots formed from human plasma incubated in vitro with Hcys (at the high concentration -3 mmol/l) have been more compact structure, with shorter and more frequently branched fibers, than those formed in the absence of Hcys (Lauricella et al 2002(Lauricella et al , 2006. Harpel et al (1992) observed that Hcys (< 8 µmol/l) enhances the binding of lipoprotein(a) to fibrin, and this results may suggest a biochemical relationship between thiol compound metabolism, thrombosis and atherogenesis.…”
mentioning
confidence: 93%
“…1 Variables known to influence fibrin clot structure include fibrinogen and thrombin concentrations, 1 pH, 2,3 ionic strength, 3 chloride ion concentration, 2 and presence of calcium ions. 4 A variety of molecules are reported to affect fibrin clot structure, including homocysteine, 5 decorin core protein, 6 heparins, 7,8 dextran, 9 and hydroxyethylstarch. 10 In this study, we demonstrate that inorganic polyphosphate (polyP) strongly modulates fibrin clot structure.…”
Section: Introductionmentioning
confidence: 99%